FORMULA TWO - DEVELOPMENTAL THEORIES AND CONTEXTS IN TEXT BOXES: Derek Hook, Jacki Watts & Kate Cockcraft (eds) (2002) Developmental psychology. Landsdowne: UCT Press. ISBN 1-919-713-689 pbk. Pages 432. - Wilbraham, Lindy (PINS-Psychology in Society, 2026)
This review article considers two local "formulae" of pedagogical developmental psychology textbooks. It reads Developmental psychology as deployment of formula two, "classical" theories with contexts hemmed into text-boxes, against (preferred) formula one, contextual issues spilled into thematic, empirical, theoretical, critical and/or historical arguments about interventions. The central interrogation of how (ex-colonized) contexts of development are made to dis/appear in relation to (universal) theory runs in several directions through textual analysis of content, form and function. First, if direct engagement with the multiple forms of South African developmental psychological praxis is avoided, how are South African student-readers hailed into its (Euro-American) truths? Second, if truths are positioned in individualistic (mostly psychoanalytic) theories, how does this "place” (which) South African contexts as "other"? Third, if truth is given to (Euro-American) deconstructions of the coercive power of theory, what can a "South African critique” be, or do? Finally, if formula one cuts deeply into specific sites/issues, and formula two sharpens theoretical tools to cut with, a combination - formula three - would be an invigorating way forward.